Development of Challenge Appraisal Scale for College Students - Zamroni Zamroni; Mihmidati Hilmia (EduLine: Journal of Education and Learning Innovation, 2023)
The study aims to develop a challenge appraisal scale for detecting a challenged attitude of students in responding to various academic challenges and difficulties in higher education. The research sample consisted of 309 students from various departments at UIN Maulana Malik Ibrahim Malang. Data analysis techniques used to evaluate the psychometric property of the scale were carried out using the item discriminating analysis, reliability analysis, and exploratory factor analysis. The results showed that the items had good discriminating power with a value range of 0.381 – 0.626, good Cronbach's alpha reliability with a value of 0.823, and the factor structure of the scale construct consisted of two aspects, namely primary appraisal and secondary appraisal with loading factor values ​​ranging from 0.578 – 0.816. Based on this study, it is known that the Challenge Appraisal Scale is suggested to have valid and reliable instrument property so that it can be used for detecting challenged attitudes of students.